Vulvar Pyogenic Granuloma in Adult Female Population: A Case Report and Review of the Literature - Nastaran Mahmoudnejad; Alireza Zadmehr; Mohammad Hamidi Madani (Case Reports in Urology)
Pyogenic granuloma (PG) is an uncommon lesion of unknown etiology. It may be formed following a minor injury. They result from a reactive or inflammatory process consisting of proliferating vascular channels, immature fibroblastic connective tissue, and scattered inflammatory cells rather than neoplastic process. Bleeding is the most common symptom of the lesion. They may be seen in all age groups, and there is no clear predominance of a gender. Vulvar PGs can be confused with other polypoid or sessile lesions of the genital site. There are only a few cases of female genital PGs reported in the literature. Herein, we describe the first case of vulvar (clitoral) PG in an Iranian patient and a brief review of the literature in this regard.